Feasibility of transnasal flexible carbon dioxide laser surgery for laryngopharyngeal lesions. Issue 5 (October 2019) - Araki, Koji; Tomifuji, Masayuki; Uno, Kosuke; Suzuki, Hiroshi; Tanaka, Yuya; Tanaka, Shingo; Kimura, Eiko; Shiotani, Akihiro
Abstract: Objective: The fiber-guided carbon dioxide (CO2 ) laser is a useful device for laryngopharyngeal surgery. The flexible CO2 wave-guide laser has been developed and commercially available for several years. However, the transnasal use of CO2 flexible wave-guided laser surgery through the instrument channel of a flexible endoscope (CO2 TNFLS) is not permitted in Japan. This feasibility study aimed to assess the value and the safety of an in-office CO2 TNFLS procedure. Methods: Patients with small laryngopharyngeal diseases were enrolled from June 2015. Eligible patients had indications with lesions generally localized superficial lesions such as the benign tumor, leukoplakia, and premalignant lesion-like carcinoma in situ (CIS). Patients were locally well anesthetized using xylocaine. After removing as much of the lesion(s) as possible with flexible forceps, the remainder of the lesions were evaporated using CO2 TNFLS through the instrument channel of a flexible endoscope under local anesthesia. Results: Eighteen surgeries involving 13 patients, including 9 papilloma (7 recurrent respiratory papilloma [RRP]), 2 carcinoma in situ, 1 leukoplakia, and 1 large epiglottic cyst), were performed. Four patients with RRP required multiple surgeries. Except for 3 patients with RRP, all patients achieved disease control without additional intervention. All procedures were completed with no severe adverse events. Conclusion: Office-based CO2 TNFLS is safe and feasible for patients with laryngopharyngeal pathologies. It is especially valuable for RRP patients with small lesions to avoid surgery under general anesthesia.